Narodziny w śmierci św. Matki Marii (Skobcowej) jako paradoksalna koncepcja duchowej i cielesnej transformacji człowieka - Ojcewicz, Grzegorz (Acta Polono-Ruthenica, 2019)
In the article the author presents the concept created by Saint Mother Maria (Skobtsova) con-cerning the birth/death and death/birth as two concurrent spiritual and physical states associated with the existence of man. Coming into the world means the end of life in the womb and death for our earthly existence means the moment of birth in eternity.